Magnetostriction enhancement of Fe73Ga27 alloy by magnetic field annealing. (1st April 2018) - Li, Xiaolong; Bao, Xiaoqian; Yu, Xin; Gao, Xuexu
Abstract: In this work, on the basis of multiphase characterics of near Ga-27 at.% alloy, magnetic field annealing was applied in a directional solidification (DS) 〈001〉 oriented Fe73 Ga27 polycrystalline alloy, and the saturation magnetostriction of 370 ppm under low magnetic field has been achieved. Large numbers of multiphase nanoparticles are precipitated in this process; also the magnetic heterogeneities are used to enhance magnetostriction. Meanwhile, this method provides an approach for developing excellent magnetostrictive materials. Graphical abstract: Image 1